Atomistic simulation studies of nanostructural titanium dioxide and its lithiation - Matshaba, Malili Gideon. (University of Limpopo (Turfloop Campus), 2013)
Titanium dioxide (TiO2) nanoparticles, nanowires, nanosheets and nanoporous are of great interest in many applications. This is due to inexpensive, safety and rate capability of the material. It has being considered as a replacement of graphite anode material in rechargeable lithium batteries. Much experimental work on pure and lithiated nanostructures of TiO2 has been reported, mostly with regards to their complex microstructures. In this work we employ molecular dynamics (MD) simulation to generate models of TiO2 nano-architectures including: nanosheet, nanoporous, nanosphere and bulk. We have successfully recrystallised all four nanostructures from amorphous precursors; calculated radial distribution functions (RDFs), were used to confirm crystallinity. Configuration energies, calculated as a function of time, were used to monitor the recrystallisation. Calculated X-Ray Diffraction (XRD) spectra, using the model nanostructures, reveal that the nanostructures are polymorphic with TiO2 domains of both rutile and brookite in accord with experiment. Amorphisation and recrystallisation was successful in generating complex microstructures. In particular, bulk and nanoporous structures show zigzag tunnels (indicative of micro-twinning) while nanosphere and nanosheet shows zigzag and straight tunnels in accord with experiment. All model nanostructures of TiO2 were lithiated with different lithium content. RDFs, microstructures, configuration energies, calculated as a function of time and XRDs of all lithiated structures are presented.
Thesis (P.hD (Physics)) --University of Limpopo, 2013
Keywords: Atomistic simulation; Nanostructural titanium dioxide; Lithiation; 669.7233; Atomic structure; Titanium dioxide; Energy storage -- South Africa